Digital Human Rights from the Perspective of Maqāṣid al-Sharī‘ah: The Urgency of Protecting Data and Human Dignity in the Age of Artificial Intelligence - Anjas Saputra; Ahmad Faidillah; Muh Ghazi Al Ghifari; Kurniati Kurniati (Ushul Al-Hukm: Jurnal Syariah dan Hukum Islam, 2025)
This research is motivated by the rapid development of Artificial Intelligence (AI), which poses new challenges to human rights, particularly regarding personal data protection and human dignity in the digital space. The objective of this study is to analyze the urgency of protecting digital human rights (DHR) in the AI era by employing the framework of Maqāṣid al-Sharī‘ah (the objectives of Islamic law). The method employed is normative-legal research with a conceptual and philosophical approach, examining the relevance of the principles of hifẓ al-nafs (preservation of self/life) and hifẓ al-nasl (preservation of offspring/future generations) in the digital context. The findings indicate that DHR, including the rights to privacy and data security, are an integral part of protecting the five fundamental Maqāṣid, particularly in ensuring individual integrity and autonomy from the threat of algorithmic manipulation and discrimination. The implication of this study is the need for the formulation of ethical AI governance policies and regulations, aligned with the values of Maqāṣid al-Sharī‘ah, to ensure that AI technology develops responsibly and upholds human dignity.